Bis(trifluoromethyl) dicarbonate, CF3OC(O)OC(O)OCF3 - García, Plácido (2005)
The synthesis of the new compound, bis(trifluoromethyl)dicarbonate, CF3OC(O)OC(O)OCF3, is carried out by reduction of bis(tri-fluoromethyl)trioxidicarbonate with excess of CO at 0 8C. The product is characterized by IR, Raman, 13C and 19F NMR spectroscopy and itsproperties are compared with those of the other members of the series CF3OC(O)OxC(O)OCF3, x = 0–3. Single crystals are grown at À25 8Cand the X-ray diffraction analysis shows the packing of syn–syn rotamers exhibiting C2 symmetry. DFT calculations predict this rotamer as themost stable one and also structural and vibrational data are predicted reasonably well.